Faktor yang mempengaruhi Tax Avoidance pada Perusahaan sektor Manufaktur yang terdaftar di Bursa Efek Indonesia - Besty Tri Minawati; Lailah Fujianti; Iha Haryani (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The Purpose of this research is to examine the effect board of commissioner, board of commissioner independent, solvability, profitability, capital intensity on tax avoidance. This research method using quantitative method. The Population in this research manufacturing sector listing in Indonesian stock exchange. Research sampling uses the purposive sampling that meet the research criteria and obtained a sample of 28 companies. The type of data is secondary data in the form company financial reports published on the website of the Indonesian stock exchange. The analytical technique used in this research is panel data regression analysis and processed using the Eviews 12 program. The results indicated that board of commissioner independent has negative effect on tax avoidance, solvability and capital intensity has positive effect on tax avoidance however board of commissioner and profitability has no significant effect on tax avoidance.